Answer:
[tex]4\frac{1}{6} + 5\frac{3}{7} = 9\frac{24}{42}[/tex]
Step-by-step explanation:
Here, the given expression is [tex]4\frac{1}{6} + 5\frac{3}{7}[/tex]
Now,a mixed fraction can be converted into unlike fraction as
[tex]a\frac{b}{c} = \frac{ac + b}{c} \\\implies 4\frac{1}{6} = \frac{4(6) + 1}{6} = \frac{25}{6}\\ 5\frac{3}{7} = \frac{5(7) + 3}{6} = \frac{38}{7}[/tex]
So, the given expression becomes:
[tex]\frac{25}{6} + \frac{38}{7}[/tex]
Now, take the LCM of the denominators 6 and 7 to make a common denominator, we get
[tex]\frac{25}{6} + \frac{38}{7} = \frac{25(7) + 38(6)}{42} = \frac{175 + 228}{42}\\ =\frac{403}{42} \\= 9.6[/tex]
Hence, on solving the given expression, we get
[tex]4\frac{1}{6} + 5\frac{3}{7} = 9\frac{24}{42}[/tex]